Survival, Virulent Characteristics, and Transcriptomic Analyses of the Pathogenic Vibrio anguillarum Under Starvation Stress - Gao, Xiaojian; Pi, Daming; Chen, Nan; Li, Xixi; Liu, Xiaodan; Yang, Hui; Wei, Wanhong; Zhang, Xiaojun (Frontiers in Cellular and Infection Microbiology, 2018)
To survive extended periods of starvation or other forms of environmental stress, many bacteria have developed strategies for metamorphosis into more or less sophisticated survival forms. As a global causative agent of vibriosis in marine fish farming, Vibrio anguillarum can efficiently grow and proliferate under environmental stress. In this study, survival, virulent characteristics and transcriptomic analyses of the pathogenic V. anguillarum were studied under starvation stress. The results showed that V. anguillarum were still culturable and showed rippled surface after six months of starvation. Starved cells maintained their infectivity for half-smooth tongue sole (Cynoglossus semilaevi) determined by injection challenges. Detection of virulence factors and virulence-associated genes in starved cells showed that the starved strain still produced β-hemolysis on rabbit blood agar, caseinase, dnase and gelatinase, and possessed empA, vah1, vah2, vah3, vah4, vah5, rtxA, flaA, flaD, flaE, virC, tonB, mreB, toxR, rpoS and ftsZ virulence related genes. In addition, we first reported the RNA-seq study for V. anguillarum the with and without starvation treatment for a period of six months and emphasize the regulation of gene expression at the whole transcriptional level. Results of this study indicated that V. anguillarum BH1 expressed 3089 and 3072 genes in control group and starvation stress group, respectively. The differently expressed genes (DEGs) of the starved strain were thereby identified, including 251 up-regulated genes and 272 down-regulated genes in comparison with non-starved strain. Gene Ontology (GO) analysis and Kyto Encyclopedia Genes and Genomes (KEGG) enrichment analysis of DEGs were also analyzed. This study suggested that long-term starved cells V. anguillarum were still culturable and pathogenic and the transcriptome sequence analysis proposed that V. anguillarum could survive under starvation stress by up-regulating or down-regulating a series of genes.